Crack propagation behaviour of carbon free and carbon bonded alumina based filter materials. Issue 8 (1st June 2020) - Neumann, Marc; Wetzig, Tony; Fruhstorfer, Jens; Lampert, Vicky; Jelitto, Hans; Schneider, Gerold A.; Aneziris, Christos G.
Abstract: The room temperature handling of ceramic foam filters for steel melt filtration strongly depends on the mechanical properties of the materials. Against this background, the filter materials Al2 O3, Al2 O3 – C, and Al2 O3 –ZrO2 – TiO2 were compared regarding the crack growth exponent n, R-curve behaviour, and energy release during crack growth. Besides, for pure alumina and alumina with zirconia and titania additions, the influence of grain size was addressed. Despite significant differences in Young's Modulus and plateau crack resistance of the R-curve, comparable n were found for Al2 O3 - and Al2 O3 –C -materials. In contrast, the behaviour of the Al2 O3 –ZrO2 – TiO2 -material differed in many regards, e.g. in the scale of n or in the energy release during crack advance. Moreover, a statistical analysis of the variances in n and the scatter of the evaluated R-curves revealed a reciprocal relation between the scatter in n and the smoothness of the found R-curves.